2015
DOI: 10.1007/s10856-015-5548-6
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of strongly attached hydroxyapatite coating on titanium by hydrothermal treatment of Ti–Zn–PO4 coated titanium in CaCl2 solution

Abstract: Hydroxyapatite (HAp) coating was formed on zinc phosphate (Ti-Zn-PO4) coated Ti plates by hydrothermal treatment in CaCl2 solution at 200 °C for 12 h. Uniform surface coverage of the fabricated HAp coating was obtained by this method. SEM-EDX analysis of the adhesion test area showed that the presence of fractures only occurred in HAp crystals. On the other words cohesive fracture was seen in HAp coating layer formed on the Ti-Zn-PO4. The measured strength was around 42.3 ± 17 MPa. Rat bone marrow (RBM) mesenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Various studies have been carried out to improve the osteoconductivity of titanium implants such as physical surface modification, surface topography, chemical treatment, coating with osteoinductive ceramics and surface photofunctionalization [14][15][16][17][18][19]. These methods are shown to be effective in increasing osteoconductivity of titanium implant.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been carried out to improve the osteoconductivity of titanium implants such as physical surface modification, surface topography, chemical treatment, coating with osteoinductive ceramics and surface photofunctionalization [14][15][16][17][18][19]. These methods are shown to be effective in increasing osteoconductivity of titanium implant.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, released Zn 2+ from sample Zn/Ca (0), representing Ca 2 SiO 3 , was close to 0, similarly to sample Ti. In previous studies [19][20][21][22], Zn, an important element in cells and the body, was introduced into an inorganic compound coating, such as hydroxyapatite (HA). To improve the osseointegration properties of the hydroxyapatite-titanium substrate (HA/TiO 2 ), Zhang et al prepared Zn containing hydroxyapatite titania (ZnHA/TiO 2 ) hybrid coatings on titanium, and the released Zn 2+ was investigated [22].…”
Section: Characterization Of Ca 2 Znsi 2 Omentioning
confidence: 99%
“…However, calcium phosphate and metal or zirconia could not make a satisfaction adherent; therefore, usage of an additive in the coating process to reinforce the coating and substrate adhesion 22) . Moreover, it was reported that a firmly adhered hydroxyapatite (HAp) layer on Ti by utilizing the zinc phosphate interface layer 23) . To approach this aim as a first step, firmly adhered zinc phosphate coating layer formed on the Ti using hydrothermal treatment 17) .…”
Section: Introductionmentioning
confidence: 99%
“…While zinc phosphatizing take place at 75-95°C for mild steel 24) , in the case of Ti and stainless steel type 316L (denoted as 316L SS) the coating could not be formed at low temperature; therefore, the hydrothermal condition was utilized to initiate the zinc phosphatizing reaction on the 316L SS 27) and Ti 17) . Then the bioactive layer was formed on the zinc phosphatized Ti by the hydrothermal method in the calcium phosphate solution 23) . On the basis of these studies, it was hypothesized that using zinc phosphate solution and hydrothermal treatment could cover the zirconia surface by a strongly adhered zinc phosphate coating layer.…”
Section: Introductionmentioning
confidence: 99%